1994
DOI: 10.1161/01.cir.90.2.818
|View full text |Cite
|
Sign up to set email alerts
|

Intensive vascular training in stage IIb of peripheral arterial occlusive disease. The additive effects of intravenous prostaglandin E1 or intravenous pentoxifylline during training.

Abstract: In a randomized open study, the combination of either prostaglandin El (PGE,) or pentoxifylline with controlled vascular training was compared with vascular training alone in patients with peripheral arterial occlusive disease in stage IIb. Forty-four patients were randomly assigned to treatment either of intensive vascular training alone (n=15) or in combination with either IV pentoxifylline (200 mg over 2 hours BID, n= 15) or PGE, (40 gg over 2 hours BID, n= 14). The basic therapy was a well-defined routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 6 publications
0
14
0
2
Order By: Relevance
“…Patients with PVD might benefit from substances causing enhanced tissue blood flow in the leg muscles [40]. This is the mechanism by which substances like the prostaglandins are believed to act [41].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PVD might benefit from substances causing enhanced tissue blood flow in the leg muscles [40]. This is the mechanism by which substances like the prostaglandins are believed to act [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several trials compared supervised exercise with pharmacological therapy, including antiplatelet medications, 96 pentoxifylline, 79,97 prostaglandin E1, 97 and iloprost. 98 Seventyseven of the 128 participants participated in supervised exercise, and 21 (16% overall; range 0% to 33%) were women.…”
Section: Supervised Exercisementioning
confidence: 99%
“…26 Although it is thought that the effectiveness of PGE1 for ASO patients mainly depends on its ability to increase peripheral blood flow via vasodilation and inhibition of platelet aggregation, some recent studies have shown that PGE1 is a potent stimulator of angiogenesis via up-regulation of VEGF expression. 27 A randomized study of 1,560 patients with chronic critical leg ischemia (Fontaine III or IV) to treatment with intravenous PGE1 or no PGE1 for 28 days 28 has shown that the combined endpoint (death, amputation, persistence of critical leg ischemia, acute myocardial infarction, or stroke) at hospital discharge was significantly lower in the PGE1-treated patients.…”
Section: Discussionmentioning
confidence: 99%